Fuzzy logic in financial analysis - Gil-Lafuente, Anna Maria. (Studies in Fuzziness and Soft Computing, 2005)
In today’s increasing complex and uncertain business environment, financial analysis is yet more critical to business managers who tackle the problems of an economic or business nature. Knowledge based on formal logic and even experience becomes less sufficient. This volume systematically sets out the basic elements on which to base financial analysis for business in the new century. It incorporates a previous work that can serve as the basis and foundation to the new contributions that are now being made in the field of financial economy and intend to provide business with instruments and models that are suitable for the treatment of the new economic context. In dealing with rapid and unpredictable changes in technological and business conditions, it postulates a growing reliance on the opinions of experts instead of past data or probabilistic forecasts, which is a radical change but may yield fruitful results. For this reason, much emphasis is devoted to the problem of aggregation of the opinion of experts in the financial field, with the object of limiting, wherever possible, the subjective component of the opinions and making sure that the decisions have the best guarantee of reaching the desired objectives. The Financial Activity of Businesses -- Basic Elements for the Treatment of Uncertainty -- Accountancy and Decision Techniques -- The Estimate of Economic-Financial Values by Means of the Budget -- Long Term Financial Solvency -- Short Term Financial Solvency -- Financial Analysis by Means of Ratios -- Risk Analysis -- Inference Chains in Financial Analysis -- The Effect of Fixed Costs on Profit -- Capital Cost -- Relation between Financial Structure and Capital Cost -- Incidence of the Financial Structure on the Value of the Business -- Sequential Study of the Modifications in the Ratio of Indebtedness -- Determination of the Possible Strategies for Reducing Indebtedness in Business -- Sequential Strategies for Raising Financial Means -- Differentiation of Financial Products -- Selection of Financial Products -- Neural Structures for the Selection of Financial Resources -- Assignment of Financial Means in Business -- The Economic-Financial Value of a Business -- The Setting up of a Financial Product -- Effects of Economic Surroundings on Financial Activity.